An Analysis of User Interface and User Experience Using System Usability Scale and GOMS Method (Universitas Negeri Semarang, 2019)
This study aims to examine user interface and user experience of Lumbung Media, online media storage of Universitas Negeri Semarang. Data were collected through a questionnaire technique by using the System Usability Scale (SUS). The obtained data were then analyzed using Goal, Operator, Methods, Selection Rules (GOMS) Analysis. SUS was used to obtain usability values and GOMS was employed to predict the time spent by users to achieve a goal on a website with a sequence of steps. The study results revealed that there is a significant improvement of Lumbung Media website before and after developed. The aspects of improvement include searching and production process. The new Lumbung Media is now more efficient and effective to be used to document instructional media.